Comparison of surgical success between two different approaches of the lacrimal pathway, External and Transcanalicular Dacryocistorinostomy, and between two different age groups. - Costa, Joana Raquel (2020)
Objective: Compare the surgical success rate ofdacryocystorhinostomy (DCR) between (1) two different techniques: External-DCR vs Transcanalicular-DCR; and comparing (2) two different age groups: <65 years vs ≥65 years.Materials and methods: Retrospective study involving 258 participants who underwent DCR between 01-01- 2014 and 31-12-2018. We define as surgical success as a total resolution of the initial symptoms analyzed:excessive tearing, blurred vision,painful swelling of medial canthus, recurrent eye infection with pus discharge; or a satisfactory resolution: participants who manifest a significant improvement and that did not consider the remaining symptoms significant to require a new surgical intervention. To answer the proposed objectives, a Pearson chi-square test was applied to compare the subjective surgical success between Transcanalicular-DCR versus External-DCR andbetween the two different age groups: <65 years versus ≥ 65 years. A P value of 0.05 or less were considered statistically significant.Results: Of the 258 patients included in the study, External-DCR were performed on 122 eyes, with surgical success reported in 90.9% of cases; 179 eyes performed transcanalicular-DCR, with a success rate of 92.2%; no significant difference was observedbetween the two techniques (p=0.712). In group aged ≥65 years, the success rate varied between 87.7%-89.6%, with a statistically significant difference, (p=0.021) compared to the higher success rates observed in the younger group (between 93.3%-97.5%).Conclusions: Both techniques, External-DCR andTranscanalicular-DCR, have high and comparable success rates. Although the success rate in the population over 65 is statistically lower than that seen in the younger population, surgical successrates remain high and without further complications.